2021
DOI: 10.1186/s13195-020-00758-4
|View full text |Cite
|
Sign up to set email alerts
|

The insulin resistance by triglyceride glucose index and risk for dementia: population-based study

Abstract: Background Insulin resistance is suggested to have negative effects on cognition; however, results from large population studies are lacking. In this study, the potential relationships between the triglyceride glucose (TyG) index, a simple surrogate marker of insulin resistance, and dementia were evaluated using a large-scale population dataset. Methods This was a retrospective, observational, cohort study using data from the National Health Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 36 publications
(20 reference statements)
0
52
0
Order By: Relevance
“…Previous evidence indicates that depression has a certain correlation with dementia and Alzheimer’s disease (AD), and clarifies the risk factors of depression which will help to further reduce dementia and AD [ 27 ]. A large cohort study found that TyG index is a risk factor for dementia, independent of traditional cardiovascular risk factors [ 14 ]. TyG is both related to depression and dementia, and we need to further explore the common mechanism between them to help block the cross-influence in depression and dementia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous evidence indicates that depression has a certain correlation with dementia and Alzheimer’s disease (AD), and clarifies the risk factors of depression which will help to further reduce dementia and AD [ 27 ]. A large cohort study found that TyG index is a risk factor for dementia, independent of traditional cardiovascular risk factors [ 14 ]. TyG is both related to depression and dementia, and we need to further explore the common mechanism between them to help block the cross-influence in depression and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existing literature [ 2 , 14 ], variables that might potentially confound between TyG index and depression symptoms are assessed: sex, age, race/ethnicity, education level. The Poverty Income Ratio (PIR) is used as a proxy measure for socioeconomic status (SES).…”
Section: Methodsmentioning
confidence: 99%
“…Recently several previous studies have proposed the triglyceride–glucose (TyG) index, calculated from fasting levels of triglycerides (TG) and glucose, as a simple, reliable and reproducible predictive indicator marker for the assessment of IR. 11 Therefore, in this study, we aimed to evaluate the value of the TyG index in the occurrence of kidney stones among the United States (US) population.…”
Section: Introductionmentioning
confidence: 99%
“…The current study was conducted to assess the association of IR with AD at KAMC-J and to study the relationship of AD with diabetes treated with insulin. There is increasing evidence to suggest that insulin irregularities and IR may play a significant role in AD pathophysiology and clinical symptoms [ 10 - 11 ]. Evidence suggests that insulin influences memory, a function mediated by the hippocampus and the adjoining medial temporal cortex [ 12 - 14 ].…”
Section: Discussionmentioning
confidence: 99%